A large‐scale meta‐analytic atlas of mental health problems prevalence during the COVID‐19 early pandemic. Issue 5 (9th January 2022) - Dragioti, Elena; Li, Han; Tsitsas, George; Lee, Keum Hwa; Choi, Jiwoo; Kim, Jiwon; Choi, Young Jo; Tsamakis, Konstantinos; Estradé, Andrés; Agorastos, Agorastos; Vancampfort, Davy; Tsiptsios, Dimitrios; et al.
Abstract: The COVID‐19 pandemic and related restrictions can impact mental health. To quantify the mental health burden of COVID‐19 pandemic, we conducted a systematic review and meta‐analysis, searching World Health Organization COVID‐19/PsycInfo/PubMed databases (09/29/2020), including observational studies reporting on mental health outcomes in any population affected by COVID‐19. Primary outcomes were the prevalence of anxiety, depression, stress, sleep problems, posttraumatic symptoms. Sensitivity analyses were conducted on severe mental health problems, in high‐quality studies, and in representative samples. Subgroup analyses were conducted stratified by age, sex, country income level, and COVID‐19 infection status. One‐hundred‐seventy‐three studies from February to July 2020 were included ( n  = 502, 261, median sample = 948, age = 34.4 years, females = 63%). Ninety‐one percent were cross‐sectional studies, and 18.5%/57.2% were of high/moderate quality. The highest prevalence emerged for posttraumatic symptoms in COVID‐19 infected people (94%), followed by behavioral problems in those with prior mental disorders (77%), fear in healthcare workers (71%), anxiety in caregivers/family members of people with COVID‐19 (42%), general health/social contact/passive coping style in the general population (38%), depression in those with prior somatic disorders (37%), and fear in other‐than‐healthcare workers (29%). Females and people with COVID‐19 infection had higher rates of almost all outcomes; college students/young adults of anxiety, depression, sleep problems, suicidal ideation; adults of fear and posttraumatic symptoms. Anxiety, depression, and posttraumatic symptoms were more prevalent in low‐/middle‐income countries, sleep problems in high‐income countries. The COVID‐19 pandemic adversely impacts mental health in a unique manner across population subgroups. Our results inform tailored preventive strategies and interventions to mitigate current, future, and transgenerational adverse mental health of the COVID‐19 pandemic. Key points: A systematic review and meta‐analysis to quantify the impact of mental health burden of COVID‐19 pandemic and related restrictions. The highest prevalence emerged for posttraumatic symptoms in COVID‐19 infected people (94%). Females and people with COVID‐19 infection had higher rates of almost all outcomes. In low‐/middle‐income nations, the prevalence of anxiety, depression, and posttraumatic symptoms is high.